If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + 5b = 52 Solving 6a + 5b = 52 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5b' to each side of the equation. 6a + 5b + -5b = 52 + -5b Combine like terms: 5b + -5b = 0 6a + 0 = 52 + -5b 6a = 52 + -5b Divide each side by '6'. a = 8.666666667 + -0.8333333333b Simplifying a = 8.666666667 + -0.8333333333b
| 0.05(x+60)-0.08(x-10)=2.9 | | 3x+4y=130 | | 4d^2+29d-60= | | 7x=52-3y | | 4x^2+33x+340= | | 3.5*0.5*1.5= | | 0.05-0.02(6-3P)=0.06(P-4)-0.28 | | 36w^2-289= | | 7x+3y=52 | | x^2+5x-90= | | x^2+4c-2=0 | | 7x-81=9 | | 4z^2+43z+108= | | -7f=f-12 | | m^2-40m+100= | | 3(x^2+10x+75)=0 | | 4-3(x+4)=5x+8 | | 7x^2+3x-12=6 | | 1/2(5x-1)=8 | | 7-x-2=12 | | 1/12x-1/4=7/6x+5/6 | | 21x-y=146 | | -2a+10+4a=5a-8a | | (3+u)(5u+7)=0 | | 3x-4=10x+12-7x | | 8x+6=-162 | | 7x+5y=0 | | 11x^2-12x-18=0 | | 11/2x-3/x | | x+(x-2)=4 | | -36-14x+49x^2=0 | | 3x+4(38-x)=130 |